M.S. VORONTSOV’S ALBUM FROM THE I.E. ZABELIN ARCHIVE: NEW INSIGHTS INTO THE GOVERNOR’S ROLE IN THE CAUCASUS - Kokorina, Ulia Georgievna; Vagabov, Mahac Mustafaevic (History, Archeology and Ethnography of the Caucasus, 2025)
This study introduces a previously underexplored historical source into scholarly discourse: an album compiled by Prince M.S. Vorontsov during his tenure as Viceroy of the Caucasus. Acquired by the prominent Russian historian I.E. Zabelin, the album is preserved in the Department of Written Sources at the State Historical Museum. The incorporation of this source into academic research enhances our understanding of the Russian Empire’s strategies for territorial expansion in the Caucasus. The significance of this study lies in its contribution to the historiography of M.S.  Vorontsov’s activities in the region, which has been characterized by diverse perspectives, ranging from admiration to critical disapproval. This work aims to refine existing knowledge by analyzing new historical material. The analysis reveals Vorontsov as a skilled military leader who valued the contributions of ordinary soldiers, a strategic administrator who advanced regional infrastructure through road and bridge construction, and a cultured individual with a deep interest in the region’s religious monuments, history, culture, and poetry. The album provides detailed insights into Vorontsov’s interactions with Shamil’s naibs and his efforts to integrate local elites into Russian service. By documenting the interactions among diverse ethnic groups within the multinational Russian state, this source offers valuable historical perspectives relevant to contemporary discussions of intercultural dynamics.
Keywords: history of Russia; Caucasian War; historical portrait; M.S. Vorontsov; I.E. Zabelin